THE SCIENTIST- VETERINARIAN IN THE MOTIVATIONAL PROCESS - Laska Angelova (Science & Research)

(untitled)
Adapting knowledge about the motivational process to the specifics of veterinary science and higher education and developing model schemes for effective motivational impact on scientific research veterinary personnel would allow a purposeful, reasoned managerial impact on human resources in the field, in sync with the needs of the relevant organizations. Subordinate to this idea is the current article, which aims to contribute to increasing the quality and competitiveness of the national veterinary science.